Impacts of dietary amino acid composition and microbial presence on preference and performance of immature Lucilia sericata (Diptera: Calliphoridae). (13th July 2018) - Rhinesmith‐Carranza, Jennifer; Liu, Wenqi; Tomberlin, Jeffery K.; Longnecker, Michael; Tarone, Aaron M.
Abstract : 1. As primary colonisers of ephemeral resources, the common green bottle fly, Lucilia sericata, must exercise efficient resource exploitation strategies to maximise fitness. Foraging incurs costs, so the efficient evaluation of resources is essential for individuals relying on fragmented patches whose dissimilarity may result in fitness consequences for offspring. Thus, selective pressures between carrion‐using insects and carrion‐associated microbes are expected to occur. 2. Microbes play a pivotal role in adult fly assessment of resources via production of volatile organic compounds (VOCs) resulting from the breakdown of essential amino acids. If one assumes that chemoreception of these VOCs provides public information regarding the corresponding essential amino acids, the resulting effects on maternal decision‐making could impact larval resource exploitation. 3. The essential amino acids phenylalanine, methionine, valine, and tryptophan, the corresponding VOCs of which are known fly attractants, were used to construct imbalanced diets with and without antimicrobial treatment to investigate the impact of suboptimal food sources on larval L. sericata . 4. The results of this study demonstrate that both amino acid composition and microbial presence influence behaviour, with larvae displaying a preference for untreated diets lacking methionine and a complete reversal in preference for antimicrobial‐treated diets. This interaction between diet and antimicrobial treatment indicates that the presence of microbes that produce essential amino acids may impact larval resource utilisation strategies. This investigation into larval performance on diets deficient in amino acids that provide important VOC cues to maternal flies provides a stepping stone for dissecting larval behavioural strategies on ephemeral resources when faced with limited choices. Abstract : Foraging incurs costs, so efficient resource evaluation is essential for primary colonisers of ephemeral resources that rely on fragmented patches whose dissimilarity may result in fitness consequences for offspring. Microbes play a pivotal role in fly assessment of resources via production of amino acid‐originating volatile organic compounds; thus, selective pressures between carrion‐using insects and carrion‐associated microbes may occur. Amino acid‐imbalanced diets were constructed with and without antimicrobial treatment to test the impact of suboptimal food sources on behaviour and performance of larval Lucilia sericata .